Changes in COVID-19 vaccine hesitancy at different times among residents in Guangzhou, China - Chen, Lu; Li, Zhi; Lu, Xiaoxiao; Deng, Yibin; Lu, Katie; Li, Tiegang; Lu, Ling; Wang, Zhiwei; Lu, Jiachun (Frontiers in Public Health, 2023)
Background Vaccination is critical to limiting the COVID-19 pandemic. However, there are still many citizens who are hesitant about this epidemic prevention measure. This article aims to understand the hesitancy rate and vaccination rate of the COVID-19 vaccine among Guangzhou residents at different points in time, and to explore the relevant factors that cause vaccination hesitancy. Methods From 2021 to 2022, a total of seven cross-sectional surveys were conducted among Guangzhou residents through the online survey software called "WenJuanXing". The survey contents included sociodemographic data, vaccination status, vaccine hesitancy and its influencing factors. Univariate analysis was performed using the chi-square test; the multivariate Logistic regression model was used to further adjust the influence of confounding factors to evaluate the factors affecting the hesitancy of the COVID-19 vaccine in different time periods. Results A total of 12,977 residents were surveyed from 2021 to 2022. The vaccine hesitancy rates fluctuated over time. From April to June 2021, the vaccine hesitancy rate showed a downward trend, from 30% to 9.1%, and then remained at 13.7% in November. However, in April-December 2022, the hesitation rate continued to rise from 13.4% to 30.1%. Vaccination rates, epidemics of disease, and changes in policies can all lead to fluctuations in vaccine hesitancy rates. The hesitancy rate is higher in low-educated, rural and workers and farmers. People with underlying medical conditions and moderate and poor self-assessed health scores were more likely to experience vaccine hesitancy. Logistic regression analysis shows that the health status of individuals is the most important factor leading to vaccine hesitancy, and secondly, residents' underestimation of domestic risks and overconfidence in personal protection measures are also related to hesitancy. At different stages, the level of hesitation among residents about vaccine side effects, safety and efficacy, and convenience have fluctuated and are influenced by varying factors over time. Conclusion In this study, we found that vaccine hesitancy fluctuated over time. Higher education, urban residents, low perceived to disease risk, and concerns about vaccine’s safety and side effects were risk factors to vaccine hesitancy. Appropriate interventions and education would be effect in improving public confidence to vaccination.